The Limits of Foreign Authority: Publicity and the Political Logic of Ambivalence in Postwar Bosnia and Herzegovina. (18th April 2017) - Gilbert, Andrew
Abstract: This article explores the ambivalent forms of authority and legitimacy articulated by the Office of the High Representative of the international community in postwar Bosnia and Herzegovina. The High Representative exercised quasi-sovereign powers that placed his position at the center of two contradictions: a democratization paradox of "imposing democracy, " that is, promoting democracy through undemocratic means, and a state-building paradox of building an independent state by violating the principle of popular sovereignty. I analyze the Office's use of mass-mediated publicity to show how the High Representative sought to legitimize his actions in ways that both sustained the norms of democracy and statehood he advocated and suspended the contradictions behind how he promoted them. In doing so, he claimed that Bosnia was caught in a temporary state of exception to the normal nation-state order of things. This claim obliged him to show that he was working to end the state of exception. By focusing on one failed attempt by the OHR to orchestrate an enactment of "local ownership" that was aimed at demonstrating that Bosnia no longer required foreign supervision, this article identifies important limits to internationally instigated political transformation. It offers a view of international intervention that is more volatile, open-ended, and unpredictable than either the ordered representations of the technocratic vision or the confident assertions that critique international intervention as a form of (neo)imperial domination. It also demonstrates the analytic importance of publicity for the comparative study of international nation-building and democratization in the post-Cold War era.